EVALUASI KINERJA METHYL DIETHANOL AMINE (MDEA) DALAM PENYERAPAN KANDUNGAN H2S PADA PROSES PENGOLAHAN GAS ALAM - . Sutanto; Ade Heri Mulyati; . Hermanto (Universitas Pakuan, 2020)
Drilling natural gas contains water vapor (H2O) and contaminant gases such as CO2 and H2S which must be removed because it reduced the calorie value of the product. H2S gas is also corrosive, easily damaging equipment so that it increased maintenance costs. The process of removing CO2 and H2S gas uses MDEA (methyl diethanolamine). This study aims to determine the optimal concentration and flow rate of absorbent methyl diethanolamine (MDEA) to absorb H2S in the plant I gas flow in Energy Equity Epic (Sengkang) Pty.Ltd. The study was carried out with a steady MDEA mix absorbent flow rate (50% pure amine and 50% demineralization water) fixed at 13 US Gallons per minute flowing continuously at the upper absorber inlet, sour gas flow rate, at the bottom of the absorber inlet with variations in the flow gas namely 7,9,11,13,15,17 MMSCFD and is contacted with amine solution counter-current. Purified natural gas (sweet gas) produced from the top absorber column outlet with an H2S content below 10 ppm. The results showed that the greater the flow rate of gas inlet, the greater the acid gas absorbed. The amount of gas entering and exiting gas follows the equation y = 0.003 x - 2.2537. The ability of the amine solution to absorb H2S follows the logarithmic equation y = 0.167 ln (x) + 101.02 with a value of R = 0.9857, y is H2S absorbed by the amine solution and x is the H2S rate.